Clinically Localized Prostate Cancer: AUA/ASTRO Guideline. Part III: Principles of Radiation and Future Directions. Issue 1 (10th July 2022) - Eastham, James A.; Auffenberg, Gregory B.; Barocas, Daniel A.; Chou, Roger; Crispino, Tony; Davis, John W.; Eggener, Scott; Horwitz, Eric M.; Kane, Christopher J.; Kirkby, Erin; Lin, Daniel W.; McBride, Sean M.; et al.
Abstract : Purpose: The summary presented herein represents Part III of the three-part series dedicated to Clinically Localized Prostate Cancer: AUA/ASTRO Guideline, discussing principles of radiation and offering several future directions of further relevant study in patients diagnosed with clinically localized prostate cancer. Please refer to Parts I and II for discussion of risk assessment, staging, and risk-based management (Part I), and principles of active surveillance and surgery and follow-up (Part II). Materials and Methods: The systematic review utilized to inform this guideline was conducted by an independent methodological consultant. A research librarian conducted searches in Ovid MEDLINE, Cochrane Central Register of Controlled Trials, and Cochrane Database of Systematic Reviews. The methodology team supplemented searches of electronic databases with the studies included in the prior AUA review and by reviewing reference lists of relevant articles. Results: The Clinically Localized Prostate Cancer Panel created evidence- and consensus-based guideline statements to aid clinicians in the management of patients with clinically localized prostate cancer. Statements regarding management of patients using radiation therapy as well as important future directions of research are detailed herein. Conclusions: This guideline aims to inform clinicians treating patients with clinically localized prostate cancer. Continued research and publication of high-quality evidence from future trials will be essential to further improve care for these men.